Nelinearna analiza razpokane armiranobetonske natezne palice - primerjava numeričnih metod - Bajc, Urška (Gradbeni vestnik, 2013)
This paper presents three numerical models for nonlinear analaysis of cracked tensile reinforced concrete bar. The first two models are based on the discrete crack method. In the first model, which is mostly reported in literature, the ideal crack is considered, while in the second discrete model the phenomenom of aggregate bridging is included. The third numerical model isbased on the smeared crack concept. This model is used to analyse the softening of reinforced concrete bar. Additionally, the crack width and their locations for all presented models are analysed. Furthermore, we analysed tension stiffness and bearing capacity of cracked reinforced concrete bar. Theresults are compared with other numerical models, based both on the discrete and smeared crack concepts. It is found out that the presented numerical model for the analysis of the behaviour of cracked tensile reinforced concrete elements accounting for aggregate bridging is well appropriate for the determination of the element tension stiffness, the crack width and also their locations. The discrete model with ideal cracks is rathergood in the same way, with the exception of the crack width. Because of the design of the model, the smeared crack model is less accurate in determining the cracks width and their locations, yet it is sufficient for thedetermination of the element tension stiffness. The results have also been compared with the values obtained by the related procedure for evaluating the width and the distance between two cracks, as given in European standard Eurocode 2. We may thus conclude that the proposed method is convenient for the evaluation of the crack width and the crack spacing in practical structural design, too.
Keywords: armiranobetonska palica; gradbeni elementi; numerični modeli; razpoke